Empowering Community Workhsop to Improve Social Welfare through Innovation in Dolok Merawan - Fadli; Paidi (Talenta Publisher, 2023)
Innovation plays an important role in realizing the ninth goal of sustainable development growths (SDGs), which focuses on increasing industrial capacity and industrial inclusiveness. Partners in this community service program are business actors in the welding workshop sector who have been running their business since 2007. Our Partners still unable to manage their finance. The failures in financial management make it difficult for partners to renew existing equipment. This condition causes the work environment to be not conducive. In addition, the lack of marketing activities means that partners have never received orders from outside their region. This community services want to solve these problems by transferring science and technology as well as additional assistance and capital provided to business actors. The involvement of students in this service program will encourage the implementation of their knowledge by carrying out learning activities outside the campus in the business world. This dedication shows a change in the behavior of business actors, especially in the field of occupational health and safety. Partners have started to separate business and household finances. Unfortunately, the optimization of business digitalization is still not optimal.